Cardio protective efficacy of Tagetes Erecta Methanolic extract in doxorubicin induced oxidative cardiac damage.: Pharmaceutical Science-Pharmacology for drug discovery - AithamrajuSatish Chandra; P. Shanmugapandiyan (International Journal of Life Science and Pharma Research, 2022)
Doxorubicin (DOX) is a highly prevalent chemotherapy agent used in the management of a wide range of cancer. However, on prolonged clinical use, DOX causes cardio toxicity and it was restricted in the clinical regimen. Tagetes erecta or marigold is a potent medical plant with many biological actions and it contains chief carotenoid known as lutein. So we have evaluated the efficacy of methanolic extract of Tagetes erecta (METE) against DOX induced cardio toxicity. Animals were randomly divided into five groups, such as control group treated with vehicle, DOX group administered with DOX 15 mg/kg, i.p, extract treated group with METE 200 and 400 mg /kg orally and Digoxin standard group for 14 days. After the experimental period, various biochemical markers were analyzed for the assessment of DOX mediated cardio toxicity. DOX intoxicated rats showed significant (p<0.05) increase in serum cardiac markers (creatine kinase, lactate dehydrogenase and Cardiac troponin-I) , lipid peroxidation and protein carbonyl content and reduced antioxidants (SOD, CAT, Gpx and GSH) level in heart tissue. Treatment with METE (200 and 400mg/kg, p.o.) restored the altered biochemical level to normalcy. Thus, the results of the study suggest that Tagetes erecta showed promising cardio protective activity in DOX induced cardiac damage mediated by its membrane stabilizing and antioxidant effect.